2016
DOI: 10.14740/jocmr2418w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Alogliptin in Patients With Type 2 Diabetes: Analysis of the ATTAK-J Study

Abstract: BackgroundDipeptidyl peptidase-4 (DPP-4) inhibitors have been shown to reduce hemoglobin A1c (HbA1c) in patients with type 2 diabetes, but the reduction varies between patients and adequate glycemic control may not be achieved. We evaluated the efficacy and safety of the DPP-4 inhibitor alogliptin in the real clinical setting, and analyzed factors associated with the improvement of HbA1c by alogliptin treatment.MethodsA retrospective observational study was performed in patients with type 2 diabetes attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Kubota et al reported that administration of sitagliptin significantly decreased TC and LDL concentrations, and tended to decrease HDL concentration in patients with type 2 DM, up to 12 weeks [9]. Takeda et al reported that administration of alogliptin significantly decreased TC and LDL concentrations in patient with type 2 DM, up to 12 weeks [20]. In our results, HDL concentration was slightly decreased in the exposure period in sitagliptin and vildagliptin users.…”
Section: Discussionsupporting
confidence: 60%
“…Kubota et al reported that administration of sitagliptin significantly decreased TC and LDL concentrations, and tended to decrease HDL concentration in patients with type 2 DM, up to 12 weeks [9]. Takeda et al reported that administration of alogliptin significantly decreased TC and LDL concentrations in patient with type 2 DM, up to 12 weeks [20]. In our results, HDL concentration was slightly decreased in the exposure period in sitagliptin and vildagliptin users.…”
Section: Discussionsupporting
confidence: 60%
“…As illustrated in the current study, DPP-4i is widely used in Japan, and this concurs with findings from other studies. For example, the ATTAK-J study reported real-world evidence of significant hypoglycaemic activity and favourable safety for DPP-4i therapy in Japanese patients with T2DM 25. The PREFERENCE 4 study documented that treatment-naive Japanese patients preferred (in terms of treatment satisfaction) a DPP-4i to a BG, SU, or α-GI 26.…”
Section: Discussionmentioning
confidence: 99%
“…As approximately 60% of such patients are treatment-naïve, DPP-4i is establishing a definitive role in the first-line treatment of T2DM in Japan 1 31. Although no significant association between DPP-4i and possible pancreatic disorder was observed in several large-scale studies,25 32–34 it is important to remain vigilant for potential safety signals35 since DPP-4i-related pancreatitis is a low but established risk 36…”
Section: Discussionmentioning
confidence: 99%
“…These findings have resulted in eight commercially available DPP-IV inhibitors, including alogliptin (Nesina ® , Vipidia ® ; Keating, 2015;Takeda et al, 2016), anagliptin , gemigliptin (Zemiglo ® ; Kim et al, 2013;Jung et al, 2014), linagliptin (Forst and Pfutzner, 2012;Barnett, 2015), saxagliptin Anderson et al, 2016), sitagliptin (Januvia ® , Xelevia ® , Glactiv ® , Tesavel ® ; Garg et al, 2013;Plosker, 2014), teneligliptin (Nakamaru et al, 2015), and vildagliptin (Galvus ® , Novartis AG; Mikhail, 2008;Richter et al, 2008), being approved and entering into the clinic . These DPP-IV inhibitors have good oral bioavailability and a relatively long duration of action in patients with T2DM.…”
Section: Dpp-iv Inhibitor and T2dmmentioning
confidence: 99%